Development of methodology for assessing steroid-tapering in clinical trials for biologics in asthma - Korn, Stephanie; Howarth, Peter; Smith, Steven G.; Price, Robert G.; Yancey, Steven W.; Prazma, Charlene M.; Bel, Elisabeth H. (Respiratory research, 2022)
Long-term use of oral corticosteroids (OCS) is associated with a risk of adverse events and comorbidities. As such, a goal in assessing the efficacy of biologics in severe asthma is often to monitor reduction in OCS usage. Importantly, however, OCS dose reductions must be conducted without loss of disease control.
Gesehen am 05.04.2022